What’s woke? Ordinary Americans’ understandings of wokeness - Benjamin M. VanDreew; Joseph B. Phillips; B. Kal Munis; Spencer Goidel (Research & Politics)
The term “woke” has evolved from its roots in the 1960s civil rights movement to a mainstream political term, most frequently used disparagingly by Republicans. Despite its frequent use, it’s unclear precisely what Americans perceive of as woke. This study investigates perceptions of woke using a conjoint survey experiment. Respondents in the conjoint are tasked with selecting the more woke list. The lists contain various attributes, identities, and policies that have, over the past few years, been branded as woke. Our findings indicate that there’s generally broad agreement among Democrats and Republicans about what is woke. However, Democratic respondents are more likely associate lower salience racially progressive and gender-progressive items as woke, while Republican respondents identify higher salience items clearly aligned with the Democratic Party as woke. Independents, as a whole, have much less consistent views, tracking more closely with Democrats when it comes to some considerations while more closely with Republicans on others.